(untitled) (Revista Brasileira de Contabilidade e Gestão, 2014)
This work has as objective show the modeling used to represent the Peg Solitaire game and detail the performance difference between different search methods used to solve the game.We usedthe depth,width, iterative depth, bidirectional, mountain climband A* searchmethods, andit was found thatdue to the largeamount ofsuccessorsthe depth searchis the most suitablefor thisproblem.Othersearch methodshave failed toreach atimelysolution.